The influence of scientific thinking and enterpreneurship toward enterpreneurship interest in physics education department students - Mahzum, E; Farhan, A; Mulia, R (Journal of physics. Conference series, 2020)
The Scientific Thinking and Entrepreneurship Course is one of the elective courses that provides entrepreneurial knowledge to students as entrepreneurship provision for students. This study aims to determine the influence of the Scientific Thinking and Entrepreneurship Course's score with the interest in entrepreneurship in Physics Education students of Teacher Training and Education Faculty, Universitas Syiah Kuala. The research method used is a quantitative method with a descriptive approach and 33 students of Physics Education who had taken the Scientific Thinking and Entrepreneurship Course in the 2016/2017 academic year was chosen as sample by purposive sampling technique. Data collection used is documentation, questionnaires and interviews. Data obtained were analyzed using regression statistics and product moment correlation. Based on the analysis, the results show that the score of the subject of Scientific Thinking and Entrepreneurship Course has little effect on the interest in entrepreneurship, it is evident from the correlation value of 0.02 and classified as a low correlation.